Green Forage Productivity, Crude Protein Yield, Seed Yield and Production Economics of Dual Purpose Ricebean (Vigna umbellata) as Influenced by Different Organic Sources of Nitrogen - Bhagyasri, G.; Kundu, C. K.; Jana, K. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted at Central Research Farm, Gayeshpur, Bidhan Chandra Krishi Viswavidyalaya, Mohanpur, West Bengal, India during kharif (June–September, 2019 and 2020) to evaluate the influence of different organic nitrogen sources on growth, quality, yield and yield parameters and production economics of dual purpose ricebean (Vigna umbellata) of Bidhan ricebean-2 variety. The experiment was laid out in Randomized Block Design (RBD) with three replications. The organic nitrogen sources used in the experiment were vermicompost, farm yard manure and biocompost. Experiment results revealed that application of 50% RDN through FYM+50% RDN through Vermicompost gave significantly higher leaf–stem ratio and drymatter accumulation. Among other treatments, with application of 50% RDN through FYM+50% RDN through vermicompost significantly highest green forage yield, dry matter yield was observed. Highest seed yield and yield attributes like pods plant-1, seeds pod-1 was observed with application 50% RDN through FYM+50% RDN through vermicompost. Application of 50% RDN through FYM+50% RDN through Vermicompost recorded highest quality parameters like crude protein, crude fat, crude fibre and crude protein yield when compared to other treatments. With respect to economics of different organic and inorganic nitrogen sources, application of 50% RDN through FYM+50% RDN through vermicompost recorded higher gross returns and net returns but higher B-C ratio was noticed with application of 100% RDN through inorganic fertilizers.